IMPROVING THE TRANSLATION ABILITY OF ENGLISH LANGUAGE TEXT INTO INDONESIAN LANGUAGES THROUGH REGISTER ANALYSIS - Km Tri Sutrisna Agustia (LPPM Universitas Dhyana Pura, 2018)
ABSTRACTTranslation of a text requires accuracy in transferring the meaning of the Source Language intoTarget Language. This led to the emergence of language variations caused by the typicalcharacteristics of the user’s needs, known as registers (Suwito, 1985: 25). The text field in thisstudy attempts to be addressed by adding the Register Analysis in the process of translatingEnglish to Indonesian. This research was carried out on students of the English Literature StudyProgram, Faculty of Economics and Humanities, semester 6 of Academic Year 2017/2018.This study aims to determine the ability of students to identify the type of register found andfind out the effect of the register analysis in the translation process before and after application.This study uses a qualitative approach in the form of case studies and uses descriptive analysismethod by observing the student work process one by one in 2 different cycles. In this studyfound types of deliberative registers based on the text used mostly taken from formal texts andnews articles. It was also found that there was an influence of the addition of an analysis registerin the translation process carried out by students which was marked by the use of appropriateterms so as to provide a high level of accuracy. So that it can be concluded that after conductingthis research found a type of formal register in text that is also formal in nature and an increasein the ability in the translation process with the addition of the analysis register process in it.Keywords: register analysis, text, accuracyABSTRAKPenerjemahan sebuah teks memerlukan keakuratan dan ketepatan dalam mengalihkan maknadari Bahasa Sumber ke dalam Bahasa Target. ini menyebabkan munculnya variasi bahasayang disebabkan sifat-sifat khas kebutuhan pemakainya, yang dikenal dengan istilah register(Suwito, 1985:25). Ranah teks dalam penelitian ini berusaha ditanggulangi denganmenambahkan Register Analis dalam proses penerjemahan teks Bahasa Indonesia ke dalamBahasa Inggris. Penelitian ini dilaksanakan pada mahasiswa Program Studi Sastra Inggris,Fakultas Ekonomika dan Humaniora semester 6 Tahun Akademik 2017/2018. Penelitian inimemiliki tujuan untuk mengetahui kemampuan mahasiswa dalam mengidentifikasi jenisregister yang ditemukan dan mengetahui pengaruh register analisis dalam prosespenerjemahan sebelum dan sesudah penerapan. Penelitian ini mengunakan pendekatankualitatif yang berbentuk studi kasus dan menggunakan metode analisis deskriptif denganmengamati proses karya penejermahan mahasiswa satu persatu dalam 2 siklus yang berbeda.Dalam penelitian ini ditemukan jenis register deliberative dan oratorical berdasarkan teksyang dipakai sebagian besar diambil dari teks formal dan artikel berita. Ditemukan jugaadanya pengaruh penambahan register analisis dalam proses penerjemahan yang dilakukanmahasiswa yang ditandai dengan penggunaan istilah yang tepat sehingga memberikan nilaikeakuratan yang tinggi. Sehingga dapat disimpuka bahwa setelah melakukan penelitian iniditemukan jenis register yang formal dalam teks yang sifatnya juga formal dan adanyapeningkatan kemampuan dalam proses penerjemahan dengan ditambahkannya proses registeranalisis di dalamnya.Kata kunci: register analisis, teks, keakuratan, ketepatan